The fractional composition calculation of two-component mixtures using direct and scattered X-rays: a new methodology testing - Badazhkov, D.; Usov, E.; Tyazhev, Anton V.; Serdyuk, D.; Tailakov, D. O.; Ulyanov, V. N.; Vinnik, A. E.; Skakunov, M. S.; Shaimerdenova, Leyla K.; Tolbanov, Oleg P.; Mashnin, A.; Spirin, A.; et al. (Journal of instrumentation : electronic journal)
Continuous monitoring and control of hydrocarbon flow is not a new task. Today, there are many engineering solutions in flow measurement that are used in commercial applications. However, the search for other solutions continues and is associated with the emergence of new technical challenges of the oil and gas industry. There is also a constant request for optimization of already working flow-metering solutions. In the present work we propose a methodology to calculate the composition of a mixture using gamma densitometry methods with direct and scattered radiation tracking. Experiments were carried out on reference samples and ways of practical implementation of the proposed methodology are shown.